2014
DOI: 10.1038/srep04340
|View full text |Cite
|
Sign up to set email alerts
|

Association between Red Blood Cell Transfusion and Bronchopulmonary Dysplasia in Preterm Infants

Abstract: Anemia and the need for transfusion of packed red blood cells (PRBCs) are common in preterm infants. PRBC transfusion increases the oxygen carrying capacity of hemoglobin and may result in higher rates of organ dysfunction. To determine whether PRBC transfusion in preterm infants is associated with an increased incidence of bronchopulmonary dysplasia (BPD), this retrospective study was performed on neonates with birth weights ≤ 1,500 g or gestational age ≤ 32 weeks admitted from August, 2008 to November, 2013.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
27
1
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(43 citation statements)
references
References 30 publications
7
27
1
4
Order By: Relevance
“…We found an association between a greater total volume of RBCs transfused and higher risk of BPD. This finding has been previously reported in prior observational studies, including a prospective observational study in the United Kingdom and more recent single‐center observational studies from China . A study from Korea found similar associations between volume and number of RBC transfusions and BPD in a univariable analysis, but no association with ferritin levels or average iron supplementation during hospitalization and BPD .…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…We found an association between a greater total volume of RBCs transfused and higher risk of BPD. This finding has been previously reported in prior observational studies, including a prospective observational study in the United Kingdom and more recent single‐center observational studies from China . A study from Korea found similar associations between volume and number of RBC transfusions and BPD in a univariable analysis, but no association with ferritin levels or average iron supplementation during hospitalization and BPD .…”
Section: Discussionsupporting
confidence: 88%
“…This finding has been previously reported in prior observational studies, including a prospective observational study in the United Kingdom 24 and more recent single-center observational studies from China. 7,25 A study from Korea found similar associations between volume and number of RBC transfusions and BPD in a univariable analysis, but no association with ferritin levels or average iron supplementation during hospitalization and BPD. 26 By contrast, a recent prospective study from Japan found hyperferritinemia (ferritin ≥500 ng/mL) to be associated with a higher risk of BPD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Exposure to prolonged anemia may have detrimental consequences on the preterm infant, contributing to complications related to prematurity and poor growth . Conversely, RBC transfusions are not without risks, including potential associations with necrotizing enterocolitis, bronchopulmonary dysplasia, retinopathy of prematurity, intraventricular hemorrhage, and adverse long‐term neurodevelopmental outcomes . Randomized controlled trial data have shown conflicting results between a liberal (higher hematocrit [Hct] threshold) versus a restrictive (lower Hct threshold) transfusion strategy with regard to short‐term morbidities and long‐term neurodevelopmental outcomes .…”
mentioning
confidence: 99%
“…1 Conversely, RBC transfusions are not without risks, including potential associations with necrotizing enterocolitis, bronchopulmonary dysplasia, retinopathy of prematurity, intraventricular hemorrhage, and adverse long-term neurodevelopmental outcomes. 1,[6][7][8][9][10][11] Randomized controlled trial data have shown conflicting results between a liberal (higher hematocrit [Hct] threshold) versus a restrictive (lower Hct threshold) transfusion strategy with regard to short-term morbidities and long-term neurodevelopmental outcomes. 3,12 Not surprisingly, transfusion practices vary greatly given the lack of clear evidence to guide transfusion strategy.…”
mentioning
confidence: 99%